Windows Media Player Remote Control (Wi.M.P.R.C) - Ali, Khairul Anwar (Universiti Teknologi Petronas, 2005)
Mobile remote control is an application embedded in mobile phone with Symbian Software Ltd Java or all Java-based enable. They can control various types ofdevices and software via Bluetooth or Infra Red connection. Most of the mobile phone application uses the Java platform known as Java 2 Mobile Edition as their programming language. In this paper, the author presents an approach to develop a Windows Media Player Remote Control (Wi.M.P.R.C) which can control basic function ofthe application such as play or pause. The main purpose of this project is to develop an application to control Windows Media Player via Bluetooth. This application will reduce the usage amount of keyboard and mouse to control the Windows Media Player and also to fully utilize the function of mobilephone for not just to talk.